Effect of dried rebon shrimp substitution on organoleptic characteristics, proximate composition, and iron content of dimsum - Linggar Puspa Virginia; Mia Srimiati (Arsip Keilmuan Gizi (AKG), 2025)
Rebon shrimp is a local food source of heme iron with relatively high iron content; however, its acceptability among adolescents remains low due to its strong odor and less appealing appearance. Processing dried rebon shrimp into dim sum may enhance both acceptability and nutritional value. This study aimed to evaluate the effect of dried rebon shrimp substitution on the organoleptic characteristics, proximate composition, and iron content of dim sum. An experimental study was conducted using a completely randomized design with five substitution levels of dried rebon shrimp: F1 (20%), F2 (40%), F3 (60%), F4 (80%), and F5 (100%). Organoleptic evaluation was performed using a 7-point hedonic scale involving 35 semi-trained panelists. Data were analyzed using the Kruskal–Wallis test followed by the Mann–Whitney post hoc test. The results demonstrated that different substitution levels significantly affected the aroma, texture, taste, and color of dim sum. The formulation with 40% dried rebon shrimp substitution showed the highest acceptability. Proximate composition and heme iron analyses of the selected formulation revealed a moisture content of 63.71%, ash content of 1.49%, carbohydrate content of 24.01%, protein content of 7.57%, fat content of 3.22%, and heme iron content of 1.20 mg/100 g. Although dried rebon shrimp substitution increased the heme iron content of dim sum, the product does not yet qualify as a source or high-heme iron food.